Pendekatan Imersi Dalam Pembelajaran Bahasa Indonesia Bagi Penutur Asing (BIPA) (Penerapan Program Imersi Di Australia) - Derri Ris Riana (Jurnal Bahasa Indonesia bagi Penutur Asing, 2020)
Various learning strategies have been carried out in BIPA teaching. One approach that is quite interesting in BIPA teaching, especially in Australia is immersion approach. Immersion approach is an approach taken to improve language skills by immersing participants in the target language, Indonesian. Therefore, the problems are how the characteristics of BIPA learners and participants of the immersion program and how the program design and implementation of the immersion program, especially in Victoria, Australia. This study aims to describe the characteristics of BIPA learners and teachers in the immersion program and describe the program design and implementation of immersion program, particularly in Australia. The results are BIPA learners and teachers in the immersion program are multicultural because the participants come from different ethnic communities with diverse cultural backgrounds. The immersion program is designed with interesting activities in the form of games, discussions, cultural materials that are able to improve Indonesian language skills and deepen the Indonesian culture of immersion program participants.